2018
DOI: 10.1177/0263617417748112
|View full text |Cite
|
Sign up to set email alerts
|

Studies on adsorption of rare earth elements from nitric acid solution with macroporous silica-based bis(2-ethylhexyl)phosphoric acid impregnated polymeric adsorbent

Abstract: For the adsorption and recovery of rare earth elements from aqueous nitric acid, solid-phase extraction resins were prepared by impregnating and immobilizing of bis(2-ethylhexyl)phosphoric acid extractant into the macroporous silica-based polymeric (SiO 2-P) particles. It was found that bis(2-ethylhexyl)phosphoric acid/SiO 2-P had higher adsorption distribution coefficient for heavy rare earth elements than for light rare earth elements. The adsorption capacity of Gd(III) was observed to be 0.315 mmol g À1 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 64 publications
3
8
0
Order By: Relevance
“…The bands at 1071 and 1048 cm − 1 of MIL-101-C50 can be attributed to symmetric P-O stretching. At lower frequencies, all phosphorous-grafted adsorbents showed a sharp peak in the range of 960-908 cm − 1 , which can be ascribed to P-O stretching [50][51][52][53]. The presence of these new peaks in the structure provides strong evidence for successful functionalization of MIL-101.…”
Section: Ftir Spectramentioning
confidence: 99%
“…The bands at 1071 and 1048 cm − 1 of MIL-101-C50 can be attributed to symmetric P-O stretching. At lower frequencies, all phosphorous-grafted adsorbents showed a sharp peak in the range of 960-908 cm − 1 , which can be ascribed to P-O stretching [50][51][52][53]. The presence of these new peaks in the structure provides strong evidence for successful functionalization of MIL-101.…”
Section: Ftir Spectramentioning
confidence: 99%
“…Recovery of rare earth elements from uranium concentrate by using cation exchange resin (Dowex 50WX8) was studied and the authors reported that the maximum REE sorption capacity was found to 82.74 mg/g which represents about 93.23% of the original capacity of the studied resin [ 15 ]. Sorption of rare earth elements from nitric acid solution with macroporous silica-based bis(2-ethylhexyl)phosphoric acid impregnated polymeric adsorbent has been studied by Shu et al [ 16 ] Their results indicated that the adsorption capacity of Gd (III) was found to be 0.315 mmol g −1 by bis(2-ethylhexyl)phosphoric acid/SiO 2 -P in 0.1 M HNO 3 . Adsorption and separation of terbium(III) and gadolinium(III) from aqueous nitrate medium has been investigated using TVEX-PHOR resin by Madbouly et al [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This FTIR deviation pattern was previously reported on Gd adsorption using D2EHPA-impregnated resins. 38 Field emission scanning electron microscopy Table 7 shows a morphological comparison of the fresh and spent PK216 resin during the adsorption studies. The size of the spent PK216-Pr, PK216-Gd, and PK216-Dy decreased by 30-40% compared to the fresh resin.…”
Section: Resultsmentioning
confidence: 99%